Fast complex arm movements in Parkinson's disease. Issue 10 (October 1986) - Berardelli, A; Accornero, N; Argenta, M; Meco, G; Manfredi, M
Abstract : Fast arm movements involving the shoulder and elbow joints have been analysed in normal controls and in patients with Parkinson's disease. The subjects were requested to draw on a graphic tablet triangles and squares of different size and shape. The patients produced a larger number of EMG burst compared with controls. The movements were accurate, and each segment of the geometric figures was performed with a roughly straight trajectory, but the time necessary to trace the geometric figures and the pauses at the vertices were prolonged. We conclude that in Parkinson's disease the disability in generating two joint ballistic movements depends on a difficulty in running motor programmes for complex trajectories.